Analizna kemija II in industrijska analiza: Navodila za vaje - Islamčević Razboršek, Maša; Kolar, Mitja (University of Maribor Press, 2023)
Analytical Chemistry II and Industrial Analysis: Exercise Instructions. The material contains instructions for the following exercises: potentiometric titration of H3PO4 with NaOH, potentiometric determination of the concentration of bromide ions, conductometric titrations, electrogravimetry, spectrophotometric determination of iron, atomic absorption spectroscopy (AAS), atomic emission spectroscopy (AES), spectroscopic determination of a benzene-toluene mixture, ion chromatography, and gas chromatography. The instructions for the exercises are written in such a way as to enable the student to work independently, since, in addition to the actual experimental work, brief theoretical principles necessary for understanding the analytical method itself are included, and sketches and diagrams of the apparatus are also included, thus facilitating the student’s understanding of the work. in the laboratory. The structure of the material is designed to guide the reader from the purpose of the work, through the basics, to practical experiments, and finally to the new concepts collected, which are of great help in studying and preparing for the knowledge test. Instructions for working safely in the laboratory, an overview of hazardous material symbols, first aid instructions, an inventory list, and selected sources from the field of chemical analysis have also been added to the instructions.